The experience of the madness in Euripides’ Orestes as a feminization process of the hero (Circe de clásicos y modernos, 2018)
In this article, I will analyze the feminization process suffered by Orestes’ main character as part of the progress of his madness. On the one hand, the origin of the disease is attributed to feminine monsters, the Erinyes, which are also the hallucination object. On the other hand, it is used when referring to Orestes’ behavior the language of the Bacchanal, a ritual performed mainly by women in Greece. From my point of view, the feminization achieves the assimilation with the Erinyes and the followers of Dionysus, thus the main character acts like them and seeks revenge and punishment.
Keywords: tragedy; madness; Orestes; woman